Short-term exposure to dimethyl fumarate (DMF) inhibits LPS-induced IκBζ expression in macrophages - Zhang, Yong; Tang, Jingshu; Zhou, Yujun; Xiao, Qiong; Chen, Qiuyu; Wang, Hongyue; Lan, Jiaqi; Wu, Lei; Peng, Ying (Frontiers in Pharmacology, 2023)
The pharmacological activity of dimethyl fumarate (DMF) in treating psoriasis and multiple sclerosis (MS) is not fully understood. DMF is hydrolysed to monomethyl fumarate (MMF) in vivo, which is believed to account for the therapeutic effects of DMF. However, several studies have provided evidences that DMF also enters the circulation, suggesting that the unmetabolized DMF may also exhibit anti-inflammation effects. Using LPS-mediated activation of RAW264.7 cells as a model of inflammation, we uncovered that short-term exposure to DMF significantly inhibits the activation and the subsequent inflammatory response of RAW264.7 cells. Analysing the expressions of transcription factors related to inflammation, we found that DMF suppresses LPS-induced IκBζ expression. Importantly, oral DMF but not oral MMF significantly inhibits IκBζ transcription in murine peripheral blood cells. Mechanistic studies revealed that DMF with strong electrophilicity can rapidly deplete intracellular reduced glutathione (GSH), activate the Nrf2-ARE pathway and inhibit the binding of STAT3 to the IκBζ promoter, thereby regulating IκBζ expression. Taken together, these results demonstrate the rapid anti-inflammatory effects of DMF in short-term exposure to macrophages, providing evidence to support the direct anti-inflammatory activity of DMF.